2023
DOI: 10.1108/agjsr-02-2023-0067
|View full text |Cite
|
Sign up to set email alerts
|

Do psycho-entrepreneurial traits and social networks matter for innovativeness among Saudi female entrepreneurs?

Abstract: PurposePsychological and entrepreneurial traits have been widely studied as explicative variables of encouraging entrepreneurial behavior, while their impact on innovative activity is less explored. This study examines whether, how and why psycho-entrepreneurial traits and social networks effect innovativeness among women firm owners.Design/methodology/approachAnalysis of data collected from 304 Saudi women entrepreneurs accompanied by business accelerators provides a wide support with some notable exceptions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…They have high self-confidence and are happier and more independent at work. Previous studies have also found that individuals with a high internal locus of control have the lowest stress level since they can change and control the situation (Jaziri and Miralam, 2023). On the other hand, the need for an achievement personality encourages entrepreneurs to strive towards achieving the direction in their business.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have high self-confidence and are happier and more independent at work. Previous studies have also found that individuals with a high internal locus of control have the lowest stress level since they can change and control the situation (Jaziri and Miralam, 2023). On the other hand, the need for an achievement personality encourages entrepreneurs to strive towards achieving the direction in their business.…”
Section: Discussionmentioning
confidence: 99%
“…Locus of control is one of the personality variables, interpreted as an individual's belief in his/her ability to control fate (Uysal et al, 2022). Jaziri and Miralam (2023) found that a high internal locus of control better predicted entrepreneurial success than the need for achievement. Both factors are driving psychological factors influencing the behaviour of entrepreneurship (Khan et al, 2021;Qazi et al, 2020;Staniewski and Awruk, 2019).…”
Section: Multiple Mediating Roles Of Need For Achievement and Locus O...mentioning
confidence: 99%